Burnout Ditinjau dari Kualitas Kehidupan Kerja pada Karyawa - Fendro Chandra; Rianda Elvinawanty (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
This study aims to determine the relationship between quality of work life and burnout. Subjects used in this study were Workers at PT Multi Sarana Medanv consisting of 94 people who were selected by using purposive sampling technique. Data were obtained from a scale to measure quality of worklife and burnout. The calculation was performed by means of testing requirements analysis (assumption test) that consists of a test for normality and linearity. Analysis of the data used was performed by Product Moment Analysis through SPSS 17 for Windows. The results of data analysis showed that r = -0,839 and p = 0.000 (p < 0.05), indicating that there was a positive relationship between burnout and turnover intention. The results of this study indicated that the contribution (R2) given to the quality of worklife to burnout intention was 70.3 %, the remaining 29.7 % were affected by other factors not examined.